Insurance in the Perspective of Islamic Law at PT Prudential Syariah Binjai - Siti Saleha; Fauzi Arif Lubis (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
In Indonesia, the majority of the population is Muslim. Therefore, product development with the existence of a new sharia insurance principle, namely sharia, is in great demand by the public because every program offered by sharia insurance services provides a guarantee against anything that is not desired by the community. . Like illness, accident, death and other things.